A New Holistic-Evolutive Approach to Pediatric Palliative Care - Bellieni, Carlo V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book illustrates why a holistic approach is important in Pediatric Palliative Care (PPC). Readers will learn this approach has a (3z(Bhorizontal(3y (Baxis, featuring the patients$1 (Bmental and physical needs, as well as their environments. It has also a (3z(Bvertical axis(3y(B: the evolutive changes of the patients throughout their development and their illness, their aspirations and fears. An evolutive (or dynamic) approach is mandatory. Each child/parent has a different experience of illness and a different path to recovery that is influenced by their age, gender, culture, but also by the state of their grief. To take care of them, we need to know the state of the subjects we are dealing with throughout their evolution in age (children) and in sorrow (both children and parents). Jung$1 (Bs and Piaget$1 (Bschemes will be of support. This book also helps caregivers to know what ethics is. It teaches a new insight on the word (3z(Bethics(3y(B: not a series of principles or norms, but an approach based on humanistic virtues. Two criteria will be proposed to this aim: an ethics based on the refusal of inauthentic behaviors (or those behaviors that are copies of animals or machines) and a new criterion that even children have some ethical duties (not based on rules, but on naturally acceptance that their sight is modulated by the presence of their parents and friends). This ethical approach is explained to caregivers in a practical mode, ready for clinical exigencies. This book is also unique because it demonstrates that PPC also involves the true care of caregivers. It will explain how to approach, measure and overcome caregivers$1 (Bburn-out. Special attention is devoted to the approach to babies$1 (Band children$1 (Bs pharmacological and non-pharmacological analgesia and sedation. Pain assessment methods will be illustrated, as well as the development of a PPC web on the territory. This text includes perinatal and neonatal PPC. The book will be of valuable support to all those intensivists, pediatricians, nurses, psychologists, physiotherapists and healthcare professionals working in PPC units.s
Part I. Communication Throughout Palliative Care -- Crucial Importance Of The Dialogue -- Certain news is indelible -- The importance of silence -- Informed Consent: Ethical And Practical Peculiarities -- Understanding The Phase Of Grief To Speak Properly To The Patient -- Phases or stages of grief -- The pathological or unresolved grief -- When should I ask for help? -- What are postponed griefs? -- It Is Difficult To Use The Word Death -- Dealing with death and babies -- Piaget's Theory: How Children Change Their Mode To Understand Throughout Their Growth -- How The Piaget Models Are Applied To The Dialogue With The Children About Death -- Special children -- Obstacles To Communication -- Desire to protect the child from distress -- Parents' emotional well-being -- Factors that influence the communication of health professionals -- Learning To Communicate According To The Patient's Character And Mood -- Bringing Your Patients Mentally Close: The Briggs Indicator -- Part II. Ethics And Palliative Care -- What Is (3z(BEthical(3y (B-- Not principles but virtues -- The drama of imitation and of being mere (3z(Bcopies of the human(3y (B-- The conditions for ethics: Reason, Realism, Empathy -- Does The Child Have Ethical Responsibilities? -- The role of coherence and imitation -- Children are not small adults -- Suicide -- Children are not allowed to choose something against their health -- Parents Cannot Choose But Children$1 (Bs Health And Wellbeing -- The Words Of Health Show That Healthcare Is (3z(BAlliance(3y (BAnd Not Mere Procedures -- Origin of the words (3z(Bmedicine(3y(B, (3z(Bhealth(3y(B, (3z(Bcare(3y (B-- What Is Health -- Health is socially helped satisfaction -- Health is possible even for the sick -- Health and loneliness are false friends -- Pain and environment limit real health -- Part III. Perinatal Care -- Treating As Human Those Who Do Not Seem Human: The Philosophical Dilemma -- Fetal Palliative Care -- Newborns: To Heal Them All, And At Any Price? -- Criteria -- The probabilistic criterion -- Best interest principle -- The least harm criterion -- The least pain criterion -- Measuring Pain And Stress -- Scales -- Other tools to measure pain -- Part IV. Therapies -- Analgesic Therapies -- Drugs -- Adjuvant analgesics -- Non-pharmacological therapies -- Distraction: Physiological Basis -- Sedation -- Drugs -- Scales -- Self-sedation -- Refractory symptoms -- Sedation is not always necessary -- Opioids In Pediatrics -- Main opioids used in pediatrics -- Recommendations -- Most common objections -- Opioid withdrawal -- When to start or continue opioids for chronic pain -- Selection, dosage, duration, monitoring and suspension of opioids -- Special Needs -- Part V. Landmarks For A Holistic-Evolutive Approach -- The Three Paradoxes Of Caring For Terminal Children -- The baby scares us -- Paradox of the contemporary flowering and death -- Paradox of inverted reason -- Paradox of the spectator's shadow (Plato$1 (Bs myth) -- Wrong Cases Of Pediatric Palliative Care -- Use of a smoky principle -- Therapeutic obstinacy -- Contagious Pain -- Caregivers$1 (Bburnout -- The pain of the parents -- A vicious circle.s
Keywords: Critical care medicine; Pediatrics; Nursing; Palliative treatment; Pain medicine; Clinical psychology; Intensive Care Medicine; Pediatrics; Nursing; Palliative Care; Pain Medicine; Clinical Psychology; Palliative Care; Child; Infant; Terminal Care; Professional-Patient Relations -- ethics; Professional-Family Relations -- ethics